Environmental awareness and environmental behavior among Malaysian - Tan, Jia Yi 1988; Choong Weng Wai, supervisor; Fakulti Geoinformasi dan Harta Tanah (2012)
Project Paper (Sarjana Muda) - Universiti Teknologi Malaysia, 2012